2015
DOI: 10.1073/pnas.1512671112
|View full text |Cite
|
Sign up to set email alerts
|

Kin discrimination between sympatric Bacillus subtilis isolates

Abstract: Kin discrimination, broadly defined as differential treatment of conspecifics according to their relatedness, could help biological systems direct cooperative behavior toward their relatives. Here we investigated the ability of the soil bacterium Bacillus subtilis to discriminate kin from nonkin in the context of swarming, a cooperative multicellular behavior. We tested a collection of sympatric conspecifics from soil in pairwise combinations and found that despite their history of coexistence, the vast majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(215 citation statements)
references
References 46 publications
8
204
0
Order By: Relevance
“…Thus, entry into the swarm promotes competitive fitness of bacteria by excluding unrelated cells and by enhancing defense against antibiotics. Similar boundary formation has also been reported for M. xanthus (121) and B. subtilis (122). The observation of discrimination in B. subtilis demonstrates that CDI and T6SS are not the only mechanisms that bacteria use for kin discrimination, as B. subtilis does not produce CDI or T6SS.…”
Section: Contact-mediated Competitionsupporting
confidence: 81%
“…Thus, entry into the swarm promotes competitive fitness of bacteria by excluding unrelated cells and by enhancing defense against antibiotics. Similar boundary formation has also been reported for M. xanthus (121) and B. subtilis (122). The observation of discrimination in B. subtilis demonstrates that CDI and T6SS are not the only mechanisms that bacteria use for kin discrimination, as B. subtilis does not produce CDI or T6SS.…”
Section: Contact-mediated Competitionsupporting
confidence: 81%
“…39-41). Notably, it has been suggested that variability in several bacterial traits, such as the production of bacteriocins (42), contact-dependent inhibition toxins (43), or colony segregation (44,45), is maintained through kin-recognition mechanisms. Typically, kin-recognition tags are considered to direct cooperative behavior only among organisms with the same tag or to direct aggressive behavior only toward organisms with a different tag.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 12 recognition groups were found, suggesting that unrelated clones were unlikely to share the recognition type by chance. Moreover, discrimination was shown to prevent cellular movement between neighboring swarms on an agar substrate (6). The data also showed that most clones found Slovenia.…”
Section: Enter Bacillusmentioning
confidence: 81%
“…Using an approach to studying microbial social evolution that stays faithful to the natural context, Stefanic et al (6) examine the kin discrimination ability of 39 B. subtilis clones found as spores in two small soil samples (Fig. 1).…”
Section: Enter Bacillusmentioning
confidence: 99%